PERAN MEDIASI KOMITMEN ORGANISASIONAL PADA HUBUNGAN QUALITY OF WORK LIFE DENGAN KINERJA KARYAWAN KOPERASI - Prameiswari, Putu Yayang Manika; Ardana, I Komang (E-Jurnal Manajemen; Vol 11 No 5 (2022)DO - 10.24843/EJMUNUD.2022.v11.i05.p07, 2022)
The aim of this study was to reveal the mediating role of organizational commitment on the relationship between quality of work life and employee performance of the Koperasi Pasar Kamboja. This research was conducted on employees of the Koperasi Pasar Kamboja, with a sample of 40 people after being determined through the saturated sample technique. Collecting data through interviews and distributing questionnaires. The data were analyzed using path analysis techniques or path analysis. The results of this study indicate that the quality of work life has a positive and significant effect on organizational commitment. Quality of work life has a positive and significant effect on employee performance. Organizational commitment has a positive and significant effect on employee performance. Organizational commitment acts as a mediating variable partially on the relationship between quality of work life and employee performance. Keywords: quality of work life; organizational commitment; employee performance